WIRELESS NETWORK SOCIALIZATION IN THE ENVIRONMENT OF MADRASAH IBTIDAIYAH NEGERI 2 BANDA ACEH - Munandar; Zikrul Khalid (Jurnal Pengabdian Bangsa, 2023)
Madrasah Ibtidaiyah Negeri 2 Banda Aceh is located under the Ministry of Religion of the Republic of Indonesia through the Aceh provincial regional office. Technology originating from smartphones and laptops has become something that is commonly used to facilitate the process of carrying out semester exams at these schools. The continuity of semester exams is an evaluation implemented by the school in assessing each student's ability to absorb subjects for 6 months. In 2022, students from grades 4 to 6 are expected to use smartphones or laptops to take semester exams complete with their respective internet quota data packages if using smartphones. This was approved by the school in its implementation after issuing several policies that had been agreed upon by the student's parents. The smartphone data package quota for each student is different, so the throughput produced on each smartphone has a different speed too. The method used in this research is an explanation by the presenter where the explanation is more about training to answer semester exam questions using a computer network system connected to the school's hotspot. The results of this community service activity are a solution to overcome problems with the internet network during semester exams. So that all students can answer the questions given by their respective class teachers.